Synthesis of Carbon-Encapsulated Cobalt Nanoparticles by Pyrolysis - Chen, Jin; Zhang, Haiyan; Li, Liping; Zhang, Li (Asian Journal of Chemistry, 2014)
Carbon-encapsulated magnetic cobalt nanoparticles have been produced by a low cost method using Co(NO3)2 as the cobalt precursor and starch as both reductive agent and carbon source. The structure, size distribution, phase composition, magnetic properties and oxidation resistance of the particles were investigated by transmission electron microscopy, X-ray diffraction, vibrating sample magnetometry and differential scanning calorimetry. The results show that the carbon-coated cobalt nanoparticles are spherical particles with a diameter of 20-40 nm. They are particles of core-shell structure with an cobalt core inside and an onion skin carbon layer outside, carbon layer can protect inner cobalt core from been oxidized, the hysteresis curves show that they are super paramagnetic materials. Furthermore, this method provides a simple way to prepare carbon coated nanoparticles with low cost.